An overview of radioisotopes study in water pollution - Ab Wahab, Siti Umi Khalthom; Sabuti, Asnor Azrin; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman (Science Publishing Corporation, 2018)
Radioisotopes can be defined as the radioactive isotopes of an element. They refer to the atoms that contain an unstable combination of neutrons and protons. The combination can occur naturally or by altering the atoms. Nowadays, radioactive materials have become major contributing pollutants for a lot of cases of disability and mortality in all over the world. They have become a serious fear of the human, environment, and aquatic organism, although they are exposed to low levels of exposure. Therefore, to overcome these problems, the effective and easier prevention strategies should be taken and encouraged by all related parties such as industries, resi-dents, and government. Radioisotope becomes as an essential part in medical, radiography and other fields of research including the environmental study. One of the applications is they can be used as the indicators in order to identify the pollutant sources. This method can be applied in surface water around industrial area and non-industrial area. As the example, the standard limit concentra-tion of Uranium is 10ppb while for Thorium is 0.50 ppb. The study regarding radioisotope usually uses analytical instruments, for example, Inductively Coupled-Plasma Mass Spectrometry (ICP-MS) and X-Ray Fluorescence (XRF). Basically, this paper will give ideas on overview of radioisotope study and reference for acquiring a better quality of surface water in the present and future by us-ing the environmental forensic study application.